2011
DOI: 10.1063/1.3662421
|View full text |Cite
|
Sign up to set email alerts
|

Indium as an efficient ohmic contact to N-face n-GaN of GaN-based vertical light-emitting diodes

Abstract: Influence of the polymer concentration on the electroluminescence of ZnO nanorod/polymer hybrid light emitting diodes J. Appl. Phys. 112, 064324 (2012) High contrast tandem organic light emitting devices Appl. Phys. Lett. 101, 133305 (2012) Influence of indium content and temperature on Auger-like recombination in InGaN quantum wells grown on (111) silicon substrates Appl. Phys. Lett. 101, 131111 (2012) White top-emitting organic light-emitting diodes employing tandem structure APL: Org. Electron. Photonics 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…5. Previously Moon et al 18) investigated the electrical characteristics of 200-nmthick In contacts on N-polar n-GaN. Based on their XPS results, they attributed the ohmic behavior to the formation of an interfacial InN phase, creating donor-like N vacancies in n-GaN.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…5. Previously Moon et al 18) investigated the electrical characteristics of 200-nmthick In contacts on N-polar n-GaN. Based on their XPS results, they attributed the ohmic behavior to the formation of an interfacial InN phase, creating donor-like N vacancies in n-GaN.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in this study, we investigated the effects of thin In interlayers on the electrical properties of Ti=Al=Au contacts. In other words, unlike previous studies where 200-nm-thick In layers were used, 18) the In layer thickness in our study varied from 3 to 10 nm. X-ray photoemission spectroscopy (XPS) examinations were performed to elucidate the annealing dependence of the electrical behavior of the samples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, different from Ga face, the ohmic contact on N-face has the disadvantages of larger contact resistivity and poor thermal stability, which seriously affect the performance of power devices [13][14][15][16]. The contact resistivity of the N-face is two orders of magnitude than that of Ga-face, and it is degraded at 300 • C. Various efforts have been done to make good ohmic contact to N-face: (a) changing metal systems to form ohmic contact [17][18][19], (b) surface pretreatments before the deposition of ohmic contact metals [20][21][22], (c) current blocking layer between metal and surface [23]. Kim et al found that O 2 plasma treatment can effectively reduce the total and sheet resistance of Ti/Al ohmic contact to N-face [24].…”
Section: Introductionmentioning
confidence: 99%